KOMUNIKASI KONSELING SEBAGAI MEDIA PARENTING - Syamsul Hadi; Dwi Widarna Lita Putri (TASÂMUH, 2017)
One of the human needs when interacting with others are communicating. Communication as human interactions is done either consciously or unconscious. The value that is contained in the communication have an effect for each individual depending on the way of understanding and building the perception of it. Humans could create the conditions it wants according to the pattern of communication that is used. Integration between the characteristics of communication and counselling has a different charge, mix of communication science with counselling, creating a feeling of parenting that is so typical. Characteristics of communication and counselling are integrated as a medium to deliver change on parenting. That is because the process of counselling has curative and preventive properties with the aim to optimise the development of the individual or the man himself, based on knowledge. Parenting as a basic foundation of the formation of psychic, emotional and behaviour. Flower growing humans as individuals are influenced by parenting that he obtained with different types of parenting, namely democracy, authoritarian parenting and permissive.